(untitled) (Bangladesh Journal of Pharmacology, 2012)
The hepatoprotective activity of wood oil of Pinus roxburghii at doses of 200, 300 and 400 mg/kg body weight were studied on rat liver damage induced by CCL4 and ethanol. The substantially elevated serum enzymatic levels of SGPT, SGOT, ALP, total bilirubin, MDA and decreased level of GSH and total protein induced by hepatotoxins were significantly restored towards normalization by the wood oil at doses of 200 and 300 mg/kg. Hepatoprotective effect of oil may be due to its inhibitory effect on free radical formation as evident by recovery of GSH contents and decreased lipid peroxidation. Light microscopy of the liver tissue further confirmed the reversal of damage induced by hepatotoxins. Phytochemical analysis revealed presence of triterpenes and steroids, which have been known for their hepatoprotective activity. The results indicate that this plant possess hepatoprotective property that support the reported therapeutic use of plant in Indian system of medicine.